(untitled) (The Review of Diabetic Studies, 2024)
As Saudi Arabia advances its healthcare transformation under Vision 2030, the demand for interprofessional collaboration in long-term care (LTC) facilities has grown substantially. Nurses and physiotherapists are central to promoting functional independence, rehabilitation, and holistic well-being among older adults and individuals with chronic conditions. This qualitative study explores the experiences, perceptions, and collaborative practices of nurses and physiotherapists working in LTC facilities across Saudi Arabia. Using a descriptive qualitative design, semi-structured interviews were conducted with twenty healthcare professionals—ten nurses and ten physiotherapists—employed in governmental and private LTC centers in Riyadh, Jeddah, and Dammam. Thematic analysis identified four overarching themes: (1) evolving professional identity and shared purpose, (2) interprofessional collaboration and communication, (3) systemic and organizational barriers, and (4) emerging opportunities for joint professional development. Participants emphasized the complementary nature of nursing and physiotherapy in supporting patient recovery, preventing functional decline, and improving quality of life. However, both groups reported persistent challenges such as staffing shortages, unclear role boundaries, limited training in interdisciplinary teamwork, and inconsistent support from facility management. Despite these challenges, optimism prevailed regarding the national shift toward integrated, patient-centered care models. Participants highlighted the potential of tele-rehabilitation, electronic health records, and multidisciplinary rounds to enhance coordination and efficiency. The study concludes that fostering collaboration between nurses and physiotherapists requires institutional commitment, policy-level support, and continued professional education. Strengthening interprofessional practice in LTC aligns with Saudi Vision 2030’s strategic goal of building a sustainable, inclusive, and high-quality healthcare system that prioritizes prevention, rehabilitation, and patient dignity.